Effects of Age and Word Frequency on Korean Visual Word Recognition: Evidence From a Web-Based Large-Scale Lexical-Decision Task - Baek, Hyunah; Gordon, Peter C.; Choi, Wonil (Psychology and Aging, 2024)
The present study examined age differences in word-frequency effects in Korean visual word recognition through a large-scale, web-based lexical-decision task. Four hundred ninety-seven adult Korean speakers in their 20s through 60s participated in the task, in which they decided the lexicality of 120 Korean words varying in frequency and 120 nonwords. Overall, both lexical-decision accuracy and response times increased with age, and more frequent words were recognized more rapidly than less frequent words. We also found significant effects of participants’ reading skill as well as age of acquisition of words. Crucially, despite older adults’ generally slower reaction times, there was no hint of any interaction between participant age and word frequency on lexical-decision times. This result adds to the literature on age-related changes in visual word recognition and provides evidence for stable word-frequency effect across the adult age spectrum. These findings are discussed with different hypotheses of lexical access and aging proposed in the literature.
Keywords: Adult; Age Factors; Aging; Decision Making; Female; Humans; Internet; Male; Middle Aged; Pattern Recognition, Visual; Reaction Time; Reading; Recognition, Psychology; Republic of Korea; Vocabulary; Young Adult; cognitive aging; Korean word recognition; lexical decision; visual word recognition; word frequency